1999
DOI: 10.1093/carcin/20.10.2003
|View full text |Cite
|
Sign up to set email alerts
|

N-Demethylation accompanies α-hydroxylation in the metabolic activation of tamoxifen in rat liver cells

Abstract: Previous work has shown that a major route of activation of tamoxifen to DNA-binding products in rat liver cells is via alpha-hydroxylation leading to modification of the N(2)-position of guanine in DNA and to a lesser extent the N(6)-position of adenine. Improved resolution by HPLC has now identified two major adducts in rat liver DNA, one of them the aforementioned tamoxifen-N(2)-guanine adduct and the other the equivalent adduct in which the tamoxifen moiety has lost a methyl group. Treatment of rats or rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…A significant proportion of the TAM--DNA adducts formed in rat liver had lost one of the TAM N-methyl groups, and evidence suggests that N-demethylation could occur either before or subsequent to a-hydroxylation (28). The ratios of dG-N 2 -TAM : dG-N 2 -N-desmethyl-TAM observed in the present trial are very similar to previous observations in liver DNA from rats administered TAM by gavage (36,37,42).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A significant proportion of the TAM--DNA adducts formed in rat liver had lost one of the TAM N-methyl groups, and evidence suggests that N-demethylation could occur either before or subsequent to a-hydroxylation (28). The ratios of dG-N 2 -TAM : dG-N 2 -N-desmethyl-TAM observed in the present trial are very similar to previous observations in liver DNA from rats administered TAM by gavage (36,37,42).…”
Section: Discussionsupporting
confidence: 88%
“…DNA was isolated from hepatic nuclei by a phenol--chloroform extraction method using conditions described previously (27). 32 P-P analysis was carried out as described in earlier publications (10,27,28). Briefly, aliquots of DNA (4 mg) were digested for 20 h with micrococcal nuclease (0.14 U, Sigma) and spleen phosphodiesterase (0.6 mU, Merck Biosciences Ltd) at 37 C, followed by nuclease P1 (0.24 U) for 1 h. The digests were then subjected to 32 P-P by incubation with 50 mCi carrier-free [g- 32 P]ATP and polynucleotide kinase (6 U) for 30 min.…”
Section: Determination Of Tam--dna Adducts By 32 P-p--tlc (Phillips Lab)mentioning
confidence: 99%
“…Experimental model systems using human recombinant enzymes have shown that SULT2A1-catalyzed sulfation of ␣-hydroxytamoxifen leads to DNA adduct formation (Shibutani et al, 1998). Furthermore, studies indicate that sulfation of ␣,4-dihydroxytamoxifen and ␣-hydro-N-desmethyltamoxifen to reactive intermediates mediates the formation of tamoxifen-DNA adducts in rats (Phillips et al, 1999). A recent study showed quantifiable levels of SULT2A1 mRNA in endometrial samples, whereas SULT2A1 activity has not been detected in the human endometrium (Rubin et al, 1999;Singh et al, 2008).…”
Section: Andersson Et Almentioning
confidence: 99%
“…It is a prodrug that is metabolized by cytochrome P450 (P450) enzymes to an array of pharmacologically active metabolites with mixed agonistic and antagonistic effects on the estrogen receptors, but P450 metabolism may also generate reactive intermediates (Phillips et al, 1999;Desta et al, 2004). CYP3A and CYP2D6 have been identified as the major enzymes involved in the principal routes of tamoxifen's hepatic metabolism, but other P450 forms (CYP1A1, CYP1A2, CYP1B1, CYP2B6, CYP2C8, CYP2C9, CYP2C19) may also contribute (Desta et al, 2004;Notley et al, 2005).…”
mentioning
confidence: 99%
“…In addition to 3 , a second major adduct and at least one additional minor adduct, which do not appear to be derived from α-hydroxytamoxifen, are found in the livers of tamoxifen-treated rats ( ). Sequential oxidation of tamoxifen to 4-hydroxytamoxifen ( 4 , Scheme , pathway B) and 4-hydroxytamoxifen quinone methide ( 5 , Scheme ) or α,4-dihydroxytamoxifen () has been proposed as a potential metabolic activation pathway of tamoxifen that may lead to DNA binding products.…”
Section: Introductionmentioning
confidence: 99%